2K + 2H2O =>2KOH + H2 ↑ (1)
K2O + H2O => 2KOH (2)
Gọi n K = a (mol) => n K2O = 2.a (mol)
=> m K =39.a (g)
M K2O = 16 + 39.2 = 94 (g/mol)
=> m K2O = 94.2.a = 188.a (g)
Có m hỗn hợp = m K + m K2O
=> m hỗn hợp = 39.a + 188.a
=> m hỗn hợp = 227.a (g)
Theo phương trình (1) , n H2 = \(\dfrac{1}{2}\) n K = \(\dfrac{1}{2}\).a = 0,5.a (mol)
M H2 = 1.2 = 2 (g/mol)
=> m H2 = 2.0,5.a = a (g)
Có m dd sau phản ứng = m hỗn hợp + m H2O - m H2
= 227.a + 200 - a
= 226.a + 200 (g)
Theo phương trình (1) , n KOH (1) = n K = a (mol)
M KOH = 39 + 16 +1 = 56 (g/mol)
=> m KOH (1) = 56.a (g)
Theo phương trình (2) , n KOH (1) = 2.n K2O = 2.2.a = 4.a (mol)
=> m KOH (2) = 56.4.a = 224.a (g)
Có m KOH = m KOH (1) + m KOH (2) = 56.a + 224.a = 280.a (g)
Có C% = 20%
=> m KOH / m dd sau phản ứng . 100% = 20%
=> \(\dfrac{280.a}{226.a+200}.100\%=20\%\)
=> \(\dfrac{280.a}{226.a+200}=0,2\)
=> 280.a = 0,2.(226.a + 200)
=> 280.a = 45,2.a + 40
=> 243,8.a = 40
=> a ≃ 0,164 (g)
=> m hỗn hợp = 0,164.227 = 37,228 (g)
=> m = 37,228
Vậy m = 37,228